Pakistan's Security and the India-US Strategic Partnership : Nuclear Politics and National Security - Shahid Hussain Bukhari, Syed (London Routledge, 2021)
"This book explores the relationship between the developing India-United States strategic partnership and Pakistan's security. It assesses India and Pakistan's areas of cooperation to show that the partnership will bring drastic changes for India's military capabilities and modernization of its forces. The book shows that, in addition to enhancing India's domestic nuclear stockpiles through the nuclear cooperation agreement, collaboration in high-tech areas such as space and innovative technologies will enable India to acquire sophisticated delivery systems. Moreover, the author argues that these advancements will enable India to destabilize the strategic balance in the region and compel Pakistan to lower the nuclear threshold. The book also briefly explores the nuclear doctrines of India and Pakistan that provide an insight into the role of nuclear weapons in maintaining deterrence in the region. To understand the power dynamics caused by the strategic partnership and their impact on strategic stability in South Asia, the author utilises the Balance of Power and the Power Transition theories. A timely analysis of the United States-India Strategic Partnership with a Pakistan angle, the book will be of interest to academics working in the fields of Asian Security, Asian Politics, especially South Asia, Strategic Studies, International Relations, Political Science, Nuclear Non-proliferation, Conflict Studies, Arms Control, and Security Studies"-- Provided by publisher
Include Bibliography and Index
Keywords: National security -- Nuclear weapons--Government policy -- Security, International